Electrophoretic deposition of polyetheretherketone/polytetrafluoroethylene on 316L SS with improved tribological and corrosion properties for biomedical applications - Imran, Ayman; Malik , Rizwan Ahmed; Alrobei, Hussein; Ur Rehman, Muhammad Atiq (Frontiers in Materials, 2024)
Introduction 316L stainless steel (316L SS) has poor wear and corrosion resistance compared to that of the Cp-Ti and Ti-6Al-4V implants [when studied under a physiological environment using phosphate-buffered saline (PBS)]. However, 316L SS implants are cost-effective. Their wear and corrosion properties can be improved by depositing biocompatible coatings. Method In this research work, a polymer coating of polyetheretherketone (PEEK) and polytetrafluoroethylene (PTFE) was deposited at optimized parameters (20 V for 3 min) on 316L SS via electrophoretic deposition (EPD). We compared the performance between of the PEEK coating and hybrid PEEK/PTFE coatings for biomedical applications. The PEEK/PTFE coating was sintered at 350°C for 30 min. Results and Discussion Scanning electron microscopy (SEM) analysis revealed that the PEEK/PTFE coating showed a uniform coating with a uniform thickness of ∼80 µm. Fourier transform infrared (FTIR) spectroscopy analysis confirmed the presence of bonds attributed to the PEEK and PTFE coatings. The PEEK/PTFE coating exhibited adequate average surface roughness (Ra) of 2.1 ± 0.2 µm with a high value of contact angle of 132.71 ± 3, indicating the hydrophobic nature of the PEEK/PTFE coating. Scratch tests evaluated that the PEEK/PTFE coating demonstrated a 7 N load, which indicated the good adhesion between the coating and 316L SS. Furthermore, the PEEK/PTFE coating demonstrated good wear resistance, capable of withstanding a 7 N load under dry conditions, and showed a specific wear rate of ∼0.0114 mm3/Nm. Electrochemical analysis conducted using the phosphate-buffered saline (PBS) solution demonstrated that the corrosion rate of 316L SS was reduced from 0.9431 mpy to 0.0147 mpy by depositing the PEEK/PTFE coating. Thus, the developed coatings present suitable wear and corrosion resistance and are thus considered for potential orthopedic applications.